The clustering of FDI in India: The importance of peer effects - Peter Nunnenkamp; Megha Mukim (Kiel Institute for the World Economy (IfW), 2011)
We assess the location choices of 6,020 foreign and non-resident Indian investors at the level of Indian districts. Employing conditional logit models, we find that clustering of FDI is driven strongly by herding among investors from both, the same and other countries of origin. However, the behaviour of non-resident Indians and German investors is strikingly different from the general pattern.
Keywords: F23; R12; 330; Location choice; FDI; country of origin; Indian districts; conditional logit; Direktinvestition; Standortwahl; Regionale Konzentration; Herdenverhalten; Ausländisch; Provinz; Indien